Multivariate approach of inter-relationships among growth, consumption and carcass traits in Nellore cattle - Cláudio Ulhôa Magnabosco; Fernando Brito Lopes; Eliane Sayuri Miyagi; Raysildo Barbosa Lôbo; Roberto Daniel Sainz (Revista Ciência Agronômica)
The objective of the present study was to analyze the phenotypic inter-relationships between growth, feed intake and carcass traits in polled Nellore cattle, as well as to determine which bulls produced the most efficient progeny. The experiment was conducted in the feedlot of the Guaporé Pecuária (Livestock) Company, OB Brand. The following traits were analyzed: initial live weight (ILW); final live weight (FLW); average daily gain (ADG); dry matter intake (DMI); gain:feed (G:F); residual feed intake (RFI); rib-eye area (REA); rump fat thickness (RF); backfat thickness at the 12th-13th rib (BF); weighted fat score (WF); and intramuscular fat percentage (IMF). Both univariate and multivariate analyses were performed to analyze the inter-relationships between the studied traits. No significant phenotypic associations were observed between growth, carcass traits and residual feed intake, while the correlation between RFI and G:F was negative. Therefore, RFI may be used to select more nutritionally efficient animals without compromising growth or adult size. The selection of bulls with progeny showing low residual feed intake is recommended, as selection for low RFI tends to improve feed efficiency without compromising growth and development.